Disassembling the celebrity figure : credibility and the incredible - Lam, Celia; Raphael, Jackie; Weber, Millicent (At the interface/probing the boundaries, 2018)
This book questions the credibility of celebrity brands, exploring how fandoms depend on perceptions and representations of authenticity. It asks how authenticity is projected by global celebrities, and how fans consume these carefully curated personas, and explores how the media breaks down barriers between celebrities and fans. It presents a discussion of celebrities as brands, exploring how their images are maintained after they pass away. It also offers analysis of the ways in which historical figures are later reconstructed as celebrities, and explores how their images are circulated and consumed across contemporary media. Ultimately, the book examines authenticity in celebrity culture by looking at fandom, media representation, branding and celebrity deaths.